Ризики політичної самоорганзації - Березинський, В. П.; Березинский, В. П.; Berezinskij, V. (My University, 2013)
The essence and peculiarities of risks of political self-organization in the context of the entropy change in the system under agriculture (traditional), industrial and post-industrial society. It is shown that the ruling in the industrial society ‘positive’ logic of social production, which includes the accumulation and distribution of wealth in the modern (post-industrial) society overlaps (superseded) ‘negative’ logic of production and distribution of risk.
Березинський В. П. Ризики політичної самоорганзації / В. П. Березинський // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОН України ; НУ ОЮА. – Одеса : Фенікс, 2013. – Вип. 48. – С. 30-39.
Keywords: суть та особливості прояву ризиків політичної самоорганізації; «позитивна» логіка суспільного виробництва; «негативна» логіка виробництва й поширення ризиків; сущность и особенности проявления рисков политической самоорганизации; «позитивная» логика общественного производства; «негативная» логика производства и распространения рисков; the nature and features of the manifestation of the political risks of self-organization; "Positive" logic of social production; "Negative" logic of production and distribution of risks